Influence of Y Zeolite Content on the Property of Zeolite Composite Materials - Son, Le Thanh; Con, Tran Hong; Huong, Nguyen Thi; Phuong, Vo Hoang (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 3, 2016)
Abstract: The materials based on organic silica and Y zeolite were synthesized from selt-assembly of polymethylhydrosiloxane, tetraethoxysilane and Y zeolite, using sodium hydroxide as catalyst. The structure characteristic and the porosity of the resultant mesoporous material were studied by SEM-EDX, XRD and the nitrogen adsorption isotherm techniques. Chemical bondings were characterized by using Fourier transform infrared spectroscope. Results indicate that the obtained materials exhibit the large surface area and porosity. Keywords: Y Z eolite, Zeolite composite, Polymethylhydrosiloxane, Tetraethoxysilane